Performance and economic analysis of a Bimetal Automatic Light Adjusting Device- Comparative studies. (November 2020) - Li, Zhiyong; Chang, Jiajia; Zhang, Sibin; Zhao, Yuqing; Gao, Jianling
Abstract: This paper presents a Bimetal Automatic Light Adjusting Device (BALAD), a device that shields sunlight through changes in the bending angle of the bimetal sheet when heated, thereby adjusting the light that enters a room. Based on an established mathematical model, BALAD results were compared with other shading systems. By analyzing the application of the BALAD in rooms in typical cities of different building climate zones in China, the results show that BALAD performed best in Haikou. Compared with a room with no shading system, the indoor heat gain was reduced by about 4% in January, and in July was nearly 37%. In Beijing, compared with a room with no shading system, BALAD could reduce the indoor heat gain by about 36.9% in July, and in January it reduced indoor heat gain by 11.9%. However, it had little effect in Harbin and Kunming. BALAD simulations with different parameters show that the length to height ratio has the greatest influence on the heat gain of the BALAD room, followed by specific bending. The correlation between different window to wall ratios and the proportion of daily heat gain reduced in the BALAD room was also analyzed. An economic evaluation shows that the BALAD has advantages compared with electrochromic glass, which only considers installation, operational and maintenance costs. Highlights: Mathematical models of rooms with different shading systems were established. The heat gain of rooms with different shading systems were compared. The influence law of different parameters on indoor heat gain in a BALAD room was analyzed. The economic comparison between BALAD and EC was preliminarily analyzed.